جاهة الإصلاح وأثرها على أمن المجتمع في ضوء الكتاب والسنة: The Concept of Reform and Its Impact on The Security of Society in Light of The Quran and Sunnah - Saeed Al-Khaldi, Mohsen Sameeh (Maʿālim al-Qurʾān wa al-Sunnah, 2019)
This paper focuses on the issue of islah (reform) of people, and the necessity of reform to be leaded by people who is free from any personal interests but vow to serve nation. This notion is vital in order to achieve security and safety for the community as well as to eradicate strife and dispersed among people. The main aim of this research is to clarify the viewpoint of Qur’an and hadith regarding the urge of reform among the people and to establish beneficial conclusion and lessons from these sacred sources. An inductive and analytical approaches based upon extensive review of literatures have been used to compile and study the concept of reform in the light of Qur’an and hadith. Certain cases are investigated such as the unresolved problem of people within courts and government departments which uphold the importance of local reform in resolving the disputes. It has also been forwarded through this research that the emphasis of Quran is focusing on the reform of family considering family as the nucleus of community. This will include a set of specific Qur’anic verses addressing the requirement of reform in Muslim community and the preservation of social fabric. While the hadith or sunnah was full of practical applications of what is mentioned in the Holy Qur’an.